Manajemen Akreditasi Madrasah Aliyah Anwarul Hasaniyyah (Anwaha) Kabupaten Tabalong: Penelitian - Syahrani; Fauziah; Halimatu Sa’diah; Helni Atillah; Isnawati; Izatul Aspia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The expiration of accreditation is often associated with the low quality of madrasahs. Madrasahs that are not yet accredited or whose accreditation has expired are frequently perceived as lacking in quality. Accreditation poses a challenge for many madrasahs, especially newly established ones. Therefore, the management of Madrasah Aliyah (MA) Anwarul Hasaniyyah, which was founded on June 20, 2022, has taken steps to obtain accreditation. MA Anwarul Hasaniyyah, under the auspices of the Anwarul Hasaniyyah Islamic Boarding School in Marindi Village, Haruai District, Tabalong Regency, South Kalimantan, has become the focus of this accreditation management effort. The results reflect the educational quality of MA Anwarul Hasaniyyah, the challenges faced during the accreditation process, and the strategies for improving its management.